Building successful university entrepreneurial centre may leverage the reputation of Universiti Putra Malaysia - Abdullah, Zulhamri; Sabran, Mohammad Shatar; Ramlan, Mohd Fauzi (2014)
Nowadays, enhancing graduate employability among public higher education institutions can be daunting thought as many universities are facing a decrease in number of graduates being employed and marketed in a highly competitive global and national market environment particularly in a developing country like Malaysia. It is a big challenge for universities to change perceptual and behavioral mechanisms in the light of enhancing graduate employability and marketability. Realizing this key issue, this paper provides a critical and conceptual view on how to lead the entrepreneurial changes in one of leading Malaysian universities. The project report shows that entrepreneurship is not about business alone (Herrmann, 2008), importantly, addressing the importance of developing entrepreneurial graduates may transform the Malaysian university into a leading Asian entrepreneurship university. Thus, this enterprise project is aim to focus on four key aspects, the market feasibility, business strategy, market strategy, financial model, and implementation plans. The PESTEL analysis is employed to provide some evidences on entrepreneurship education which identifies the role of entrepreneurial centre as a key entity in improving the university entrepreneurial system. Specifically, vision, context, opportunity, and resources and finance are thoroughly highlighted to articulate the sound entrepreneurial education. Indeed, the impact on entrepreneurship education is emphasized on three key aspects such as the behaviorial action of students and staff, infrastructural development, and institutional changes on the eco-system of university. Thus, building the university entrepreneurial centre may leverage the reputation of Universiti Putra Malaysia.